DAMPAK DISIPLIN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING PADA SWALAYAN 88 - Hardana, Ali; Hasibuan, Lismawati; Utami, Try Wahyu (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
Payment or gift compensation is also very important attention in increasing morale employees so that it will be achieved later the expected work results will even be obtained enhanced by giving compensation according to the level of risk of each job. This study aims to examine the extent to which work discipline, compensation determines performance employees with work motivation as an intervening variable at Supermarket 88, by using quantitative research methods with data analysis techniques with path analysis to visitors as many as 268 respondents who were sampled from a population of 268 visitors, which testing the data using the SPSS 21 software tool. The results of the study are; Work discipline has a significant effect on work motivation with a direct influence coefficient of discipline work on work motivation. Compensation has no significant effect on work motivation with the direct effect coefficient of compensation on work motivation. Work discipline has a significant effect on employee performance with a coefficient of influence work discipline directly on employee performance. Compensation has that effect significant effect on employee performance with a direct effect coefficient of compensation on performance employee. Work motivation has a significant influence on employee performance with the coefficient of direct influence of work motivation on employee performance. Coefficient value indirect influence direct influence. So that work discipline has an effect significant effect on employee performance through work motivation. Or it could also be concluded that motivation work as an intervening variable in mediating the relationship between work discipline and employee performance. The value of the coefficient of indirect effect direct effect. So compensation significant effect on employee performance through work motivation. Or it could also be concluded that work motivation as an intervening variable in mediating the relationship of compensation to employee performance.